Academic Freedom: a Choice Between Conservative or Liberal Perceptions – the Case of the United States - Maćkowska, Katarzyna Teresa (Review of European and Comparative Law, 2020)
It is only the minimum extent to which the law becomes the instrument of coping with social tautness regarding the academic freedom. On the one hand, legal provisions significantly limit the number of cases related to hate crimes but on the other, they sometimes narrow a discussion due to difficulties in harmonizing individual’s rights and campuses’ perception - a phenomenon, which in the U.S. had been called as “chilling” the freedom. Undoubtedly, the enactment of free speech or academic freedom regulations at universities is necessary as it helps to prevent from a “hate speech” but the legal shape of this process has been strictly connected to a determination for either liberal or conservative description of the academic freedom. Regarding the newest Niche’s rankings, ten universities have been selected, five out of the most liberal and five the most conservative public ones. Furthermore, two catholic universities have been added to describe differences in defining the academic freedom. Moreover, some references have been made to the U.S. Supreme Court decisions, and the very fundamental documents, namely the 1940 Statement and Harvard Free Speech Guidelines. In the separate article a problem of legislative acts that had been enacted for the past two years in a response to Report of the Committee on Freedom of Expression by the University of Chicago of 2014 will be covered. A few remarks upon this matter have been hereby made, though. The article is based on a dogmatic legal method, including quotations of legal sources and their subsequent analysis.